2008
DOI: 10.1590/s0034-89102008000400007
|View full text |Cite
|
Sign up to set email alerts
|

Violência física e fatores associados: estudo de base populacional no sul do Brasil

Abstract: OBJECTIVE:To estimate the prevalence of physical violence and its association with sociodemographic aspects, stressful life events, and the use of health services due to emotional problems. METHODS:A cross-sectional population-based study was conducted with a sample of 1,954 14-year-old or older inhabitants of the city of Canoas (Southern Brazil). They were selected by means of conglomerate sampling according to a pre-established system. Data were obtained in visits to households by means of a confi dential se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
2
3
0
11
Order By: Relevance
“…In this manner, it can be said, based on the results found, that women who live with repetitive IPV present higher frequency of use of healthcare services and more health problems, especially mental health, which is confirmed by another Brazilian study 14 . Thus, Fanslow and Robinson (2004) 21 in a population-based study showed that women from 15 to 49 years of age who reported IPV presented a two-fold higher odds ratio for going to healthcare facilities in the four weeks before the investigation than those who did not report violence episodes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this manner, it can be said, based on the results found, that women who live with repetitive IPV present higher frequency of use of healthcare services and more health problems, especially mental health, which is confirmed by another Brazilian study 14 . Thus, Fanslow and Robinson (2004) 21 in a population-based study showed that women from 15 to 49 years of age who reported IPV presented a two-fold higher odds ratio for going to healthcare facilities in the four weeks before the investigation than those who did not report violence episodes.…”
Section: Discussionsupporting
confidence: 66%
“…There are few studies available on the prevalence of these women among users of certain healthcare facilities 7,8,10,13 and even one population-based study that showed the frequency of visits due to emotional problems and psychiatric hospitalizations 14 , did not show any other use pattern. In view of this picture, the present study sought to estimate the association of intimate partner violence with an increased use of primary health care in São Paulo, seeking to describe this use, in terms of demand for care.…”
Section: Introductionmentioning
confidence: 99%
“…A violência interessa aos profissionais da área de saúde, porque, dentro do conceito ampliado de saúde, tudo o que significa agravo e ameaça à vida, às condições de trabalho, às relações interpessoais e à qualidade da existência faz parte do universo da saúde pública. Além disso, a violência, num sentido mais restrito, afeta a saúde e frequentemente produz a morte (Palazzo et al 3…”
Section: Introductionunclassified
“…No entanto, o que pretendemos colocar em discussão, neste trabalho, são as manifestações excessivas de agressividade, por isso patológicas, as quais, pelas consequências de seu poder de destruição, têm mobilizado vários segmentos da sociedade e dado origem a diferentes publicações de interesse médico-odontológico (Schraiber et al2 2006, Palazzo et al3 2008).…”
unclassified
“…Estes, enquanto referenciais dos comportamentos e atuação social de homens e mulheres, levam os homens a silenciar sobre suas questões de saúde, a menos que sejam consideradas graves (Figueiredo, 2008), e levam as mulheres a falar sobre e se queixar de suas emoções, procurando auxílio nos serviços de saúde para lidar com elas (Ludermir et al, 2008). "[...] a sociedade apresenta uma maior tolerância para mulheres depressivas e homens alcoólicos do que o inverso" (Rabasquinho et al, 2007, p.439).…”
Section: Homens E Sofrimento Mentalunclassified